2017
DOI: 10.1080/02640414.2017.1378494
|View full text |Cite
|
Sign up to set email alerts
|

Effects of mild running on substantia nigra during early neurodegeneration

Abstract: Moderate physical exercise acts at molecular and behavioural levels, such as interfering in neuroplasticity, cell death, neurogenesis, cognition and motor functions. Therefore, the aim of this study is to analyse the cellular effects of moderate treadmill running upon substantia nigra during early neurodegeneration. Aged male Lewis rats (9-month-old) were exposed to rotenone 1mg/kg/day (8 weeks) and 6 weeks of moderate treadmill running, beginning 4 weeks after rotenone exposure. Substantia nigra was extracted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 50 publications
0
13
0
Order By: Relevance
“…Huang et al show that 8-week running exercise in mice can activate the autophagy pathway and improve lysosomal biogenesis, suggesting improvement in brain function of mice; besides that, they also observed that prolonged physical exercise promoted nuclear translocation of transcription factor EB (TFEB-main regulator of autophagic and lysosomal biogenesis) in the cortex, positively regulating the transcription of genes associated with autophagy and lysosome (lysosomal degradation is a fundamental step to completing the autophagy process) (188). It has also been observed that moderate exercise contributes to the prevention of early neurodegeneration in the substantia nigra region in aged rats by improving autophagy and mitophagy (189).…”
Section: Influence Of Physical Exercise In the Autophagy Process In Amentioning
confidence: 96%
“…Huang et al show that 8-week running exercise in mice can activate the autophagy pathway and improve lysosomal biogenesis, suggesting improvement in brain function of mice; besides that, they also observed that prolonged physical exercise promoted nuclear translocation of transcription factor EB (TFEB-main regulator of autophagic and lysosomal biogenesis) in the cortex, positively regulating the transcription of genes associated with autophagy and lysosome (lysosomal degradation is a fundamental step to completing the autophagy process) (188). It has also been observed that moderate exercise contributes to the prevention of early neurodegeneration in the substantia nigra region in aged rats by improving autophagy and mitophagy (189).…”
Section: Influence Of Physical Exercise In the Autophagy Process In Amentioning
confidence: 96%
“…Current knowledge about the mechanism of the neuroprotective properties of physical training on the functional state of dopaminergic neurons is based on data obtained from animal studies. Many of these studies suggest that exercise can prevent or slow down neurodegenerative processes and rebuild disturbed signaling pathways [1113]. The neuroprotective effect of physical training is associated with the activation of the neurotrophin signaling pathways [14, 15], synaptogenesis [16], angiogenesis [17] and neurogenesis strengthening [18, 19], reduction of inflammatory processes [2022], and stabilization of calcium homeostasis [23].…”
Section: Introductionmentioning
confidence: 99%
“…Using the rotenone model, it has been shown that early aerobic exercise for 2 or 6 weeks was effective to prevent elevated αsynuclein levels while increasing tyrosine hydroxylase levels in the substantia nigra. 36,37 In addition, aerobic exercise for 2 weeks following rotenone exposure was found to reduce the loss of serotonergic markers in the dorsal raphe and mitigate depressive behaviors. 38 Rats that receive aerobic exercise following rotenone exposure also demonstrate improved motor performance in the rotarod test compared to sedentary rats, 37 suggesting preservation of motor function in exercising animals.…”
Section: Rationale For Neuroprotective Effects Of Exercise In Prodrommentioning
confidence: 99%
“…In summary, evidence from aerobic exercise trials in early PD, as well as in parkinsonian animal models, suggests that aerobic exercise may impart beneficial effects on motor function by preserving dopaminergic and corticostriatal systems in the presence of disease. 36,37,46 For a review of aerobic exercise in PD, please see Schootemeijer et al 32 Prescription of aerobic exercise in iRBD should include factors of intensity, duration, and frequency. Moderate-to high-intensity exercise with a duration of 30 to 45 minutes a minimum of 3 times per week is recommended.…”
Section: Exercise As An Intervention For Prodromal Synucleinopathymentioning
confidence: 99%